Testing creative destruction in an opening economy. Issue 3 (5th April 2013) - Aghion, Philippe; Fedderke, Johannes; Howitt, Peter; Viegi, Nicola
Abstract This paper analyses the relationship between trade liberalization and economic growth using a Schumpeterian framework of technological innovation and applies it to sector‐level South African data. The framework examines direct and indirect effects of trade liberalization on productivity growth. Indirect impacts operate through a differential impact of trade liberalization on firms conditional on their distance from the international technological frontier. Results confirm positive direct impacts of trade liberalization. Results confirm also that the greatest positive impact of trade liberalization will be on sectors that are close to the international technological frontier and that experienced a low level of product market competition before liberalization.